Morphological characteristics of pinna bicolor gmelin and pinna deltodes menke from the seagrass bed of Sungai Pulai, Johor, Peninsular Malaysia - Idris, Mohd Hanafi; Arshad, Aziz; Bujang, Japar Sidik; Abd. Ghaffar, Mazlan; Daud, Siti Khalijah (2009)
Samples of Pinna bicolor Gmelin and Pinna deltodes Menke were collected from the seagrass bed of Sungai Pulai, covering Merambong shoal, Tanjung Adang shoal and Merambong Island off south western coast of Johor, Malaysia for morphological study from August 2005 to June 2006. It was observed that P. deltodes is associated with hard substratum and P. bicolor is associated with soft substratum in the study area. Physically there was no difference between P. bicolor and P. deltodes. The species were identified on the basis of nine internal and external characteristics of the valves. The two species were found to be morphologically different on the basis of width of sulcus, distance between posterior adductor muscle to posterior dorsal nacreous layer, dorsal posterior margin length and shell width.